Anti-SARS-CoV-2 RBD IgG responses in convalescent versus naïve BNT162b2 vaccine recipients. Issue 18 (28th April 2021) - Azzi, Lorenzo; Focosi, Daniele; Dentali, Francesco; Baj, Andreina; Maggi, Fabrizio
Highlights: Vaccination campaigns anti SARS-CoV-2 have been recently launched worldwide. Most countries are vaccinating convalescents and naïve subjects with the same schedule. Most health systems are suffering shortages of vaccines. Usage optimization of the existing stockpiles has been hypothesized.